Looking for signatures of sex-specific demography and local adaptation on the X chromosome - Heyer, Evelyne (BioMed Central, 2010)
A population study comparing X-linked variation with that of the autosomes reveals that social organization has a clear impact on X chromosome genetic diversity and that the X chromosome shows a signature of local adaptation. See related research article: http://genomebiology.com/2010/11/1/R10.